Optimalisasi Kinerja Kader Posyandu melalui Program Pelatihan Komunikasi dan Manajerial Berbasis Pemberdayaan untuk Pencegahan Stunting - Rudi Wibowo; Ali Basah; Erna Nur faizah; Nuning Nurna Dewi (Jurnal Pengabdian Masyarakat Nusantara, 2026)
This Community Service (PKM) activity aims to improve the performance of Posyandu cadres in stunting prevention efforts in Kepudibener Village, Turi District, Lamongan Regency. The main problems faced by the community include low health literacy, suboptimal utilization of Posyandu, and limited capacity of cadres in providing health education. The implementation method uses a participatory and educational approach through the stages of observation, cadre training, health education, mentoring, and program evaluation. The results of the activity show an increase in the knowledge and skills of Posyandu cadres in monitoring child growth and development and nutrition education, increased community participation in Posyandu activities, and an increase in understanding of mothers of toddlers regarding stunting prevention. This program is also able to strengthen the role of cadres as agents of change in raising community awareness of the importance of family health. Thus, improving the performance of Posyandu cadres has proven effective in supporting community-based stunting prevention efforts. Sustainability of the program through ongoing training and mentoring is essential to maintain the positive impacts that have been achieved.